The Biological Functions and Clinical Significance of SARS-CoV-2 Variants of Corcern - Akkız, Hikmet (Frontiers in Medicine, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is continuing to evolve, emerging novel variants with spike protein mutations. Although most mutations emerged in the SARS-CoV-2 genome are neutral or mildly deleterious, a small number of mutations can affect virus phenotype that confers the virus a fitness advantage. These mutations can enhance viral replication, raise the risk of reinfection and blunt the potency of neutralizing antibodies triggered by previous infection and vaccination. Since December 2020, the SARS-CoV-2 has emerged five quickly spreading strains, designated variants of concern (VOCs), including the Alpha (B.1.1.7) variant, the Beta (B.1.351) variant, the Gamma (P.1) variant, the Delta (B.1.617.2) variant and the Omicron (B.1.1.529) variant. These variants have a high number of the mutations in the spike protein that promotes viral cell entry through the angiotensin-converting enzyme -2 (ACE2). Mutations that have arisen in the receptor binding domain (RBD) of the spike protein are of great concern due to their potential to evade neutralizing antibodies triggered by previous infection and vaccines. The Alpha variant emerged in the UK in the second half of 2020 that has spread quickly globally and acquired the E484K mutation in the UK and the US. The Beta and Gamma variants emerged in South Africa and Brazil, respectively that have additional mutations at positions E484 and K417 in the RBD. SARS-CoV-2 variants containing the combination of N501Y, E484K, and K417N/T mutations exhibit remarkably decreased sensitivity to neutralizing antibodies mediated by vaccination or previous infection. The Gamma variant may result in more severe disease than other variants do even in convalescent individuals. The Delta variant emerged in India in December 2020 and has spread to many countries including the US and the UK. The Delta variant has 8 mutations in the spike protein, some of which can influence immune responses to the key antigenic regions of RBD. In early November 2021, the Omicron (B.1.1.529) variant was first detected in Botswana and South Africa. The Omicron variant harbours more than 30 mutations in the spike protein, many of which are located within the RBD, which have been associated with increased transmissibility